The use of the Valsalva manoeuvre in the evaluation mechanisms regulation of cardiovascular system - study case - Anna Maria Dobosiewicz; Paulina Miętkowska; Agnieszka Marszałek; Sylwia Wendland; Piotr Chyba; Grzegorz Duda; Szymon Kwiatkowski (Kazimierz Wielki University, 2017)
Valsalva maneuver is one of the method, with which we can evaluate the parasympathetic nervous system. The person who is doing the maneuver need to conduct a maximal, forced expiration against a closed glottis. During the maneuver we can observe very important changes in the cardiovascular system. The changes can be separated into four phases. The cardiovascular system can be observed by using Task Force Monitor®. The aim of the work  is to present a case study of a young man, 22-years old, who did the Valsalva maneuver.  Valsalava maneuver can give interesting and valuable information about the organism of the person who is doing the maneuver.